Diş Aşınmaları Nedeniyle Dikey Boyut Kaybı Oluşan Hastanın Direkt Kompozit Restorasyonlar İle Rehabilitasyonu (Olgu Sunumu). - Yasser İsmail Al Rawi; Ali Rıza Çetin (Selçuk University, 2019)
Özet: Diş aşınmaları yaşlı hastalarda en sık karşılaşılan durumlardan biridir. Dikey boyut kaybı nedeniyle hem fonksiyonel hem de estetik problemleri neden olmaktadır. Normal dikey boyutu yeniden kazanabilmek için birkaç tedavi seçenekleri vardır. Sunulan vakada 51 yaşındaki erkek hastada yaygın diş aşınmaları ve çiğneme fonksiyonunda sorunlar mevcuttu. Dikey boyutun geri kazanılması amacıyla premolar dişlerin restorasyonu ile dikey boyut düzenlenmiş ve posterior dişler için implant destekli sabit protez yapılması planlanmıştır. Hastanın estetiğini düzeltmek, fonksiyona katkı sağlamak ve dikey boyutunun alışmasını kolaylaştırmak için üst alt anterior dişlere kompozit veneer restorasyonlar yapılmıştır. Bu restorasyonlar rehabilitasyonun ilk aşamasını oluşturacak ve hastanın planlanan tedavi sürecine alışmasını ve konforunu artıracaktır.Anahtar kelimeler: Diş Aşınmaları, Dikey Boyut Kaybı, Dental Kompozit.  Abstract: Teeth wear is one of the most common conditions seen in elderly patients. Loss of normal occlusal vertical dimension can severely affect both function and esthetic. There are many approaches to regain the normal occlusal vertical dimension. In the presented case a 51 years old male patient had severe tooth wear in the maxillary and mandibular anterior teeth with loss of interocclusal space due to early loss of his posterior teeth. In order to regain the vertical dimension, premolar teeth were restored with composite restoration and the vertical dimension corrected for some extent, implant-supported fixed prosthesis was planned for the posterior area. For the anterior teeth, composite veneer restorations were made to upper and lower teeth in order to provide esthetic, function and to facilitate the patient's adaptation of the increased vertical dimension. These restorations will create the first stage of rehabilitation and will increase the adaptation and comfort of the patient in the planned treatment process. Keywords: Tooth wear, Vertical Dimension Lose, Dental Composite.